Implementasi Business Intelligence untuk menganalisis Perkembangan Akademik Mahasiswa di Program Studi Sistem Informasi UNISNU Jepara - Margaretha, Sintikhe Novia; Azizah, Noor; Sabilla, Alzena Dona (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2024)
This research aims to build a Business Intelligence (BI)-based academic monitoring system in the Unisnu Jepara Information Systems Study Program to improve the efficiency and quality of decision making. The method used involves analyzing student academic data with the help of Microsoft Power BI for data processing. Data is taken from the Academic Information System (SIAKAD) and processed to produce visualizations in the form of informative dashboards. The research results show visualization of academic data which includes the number of students, academic status, average GPA, study period, and graduate success. This dashboard makes it easier to monitor and analyze academic data, supports better decision making, and improves the quality of education in the Unisnu Jepara Information Systems Study Program. This research makes aware how important BI implementation is in optimizing academic data management and strategic decision making in